Austenitic stainless steel with high product of strength and elongation and high corrosion resistance and preparation method thereof
By introducing nanotwin and recrystallized grains into stainless steel and adopting the warm rolling + interrupt solid solution process, the problem of difficult corrosion and strength and plasticity of existing stainless steel materials in extreme environments is solved, and austenitic stainless steel materials with high strength, high plasticity and high corrosion resistance are achieved, which are suitable for traffic safety facilities of highway guardrails.
Patent Information
- Application Number
- CN202510471477.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-15
- Publication Date
- 2025-06-24
AI Technical Summary
Existing stainless steel materials are prone to corrosion in extremely harsh environments, and it is difficult to have both high strength and high plastic toughness. The processing performance is insufficient, which affects the service performance and safety of highway guardrails.
High-strength plasticization and high corrosion-resistant austenitic stainless steel are used, and its chemical compositions include C, Mn, Cr, Ni, P, S, N, Cu, etc. Through the warm rolling + interrupt solid solution process, nanotwins and recrystallization grains are introduced, layering is wrong and controllable α'-martensite phase transformation is improved, tensile strength, elongation after break and strong plasticization are improved.
The coordinated improvement of tensile strength ≥1100MPa, elongation after break ≥55% and strong plastic accumulation ≥65 GPa·% has been achieved, which reduces material costs, improves corrosion resistance and processing performance, and is suitable for traffic safety facilities of highway guardrails.
Smart Images

Figure CN120193216A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of austenitic stainless steel production, and specifically relates to a high-strength and high-ductility product high-corrosion-resistant austenitic stainless steel and a preparation method thereof. Background Art
[0002] Facing the complex structural design of highway guardrail stainless steel and the complex service environment of highways, there is an urgent need to develop high-strength and high-ductility stainless steel with more excellent comprehensive performance for the lightweight and high-quality service performance of highway guardrails. High-strength and thickness reduction for lightweighting can have a significant effect on economy, but it will affect the stiffness, processing performance and corrosion resistance of steel materials, and further affect the safety factor of highway guardrail traffic safety facilities. Therefore, exploring a dual material design concept that combines the ideas of "high strength and high ductility product" and "high corrosion resistance" has important research significance and practical value for breaking through the bottleneck of highway guardrail stainless steel materials.
[0003] 1. Problems and Disadvantages of the Existing Technology (1) Insufficient Corrosion Resistance In extremely harsh environments or highway environments where snow melting agents are frequently used in winter, traditional stainless steel materials for highway guardrails are prone to corrosion. Although some existing stainless steels have certain corrosion resistance, their resistance to pitting and crevice corrosion is limited in the face of high-concentration chloride environments. For example, after several years of use on coastal highways, obvious rust spots will appear on the surface of ordinary 304 stainless steel, resulting in material failure and affecting the stability and safety of the guardrail.
[0004] (2) Difficulty in Simultaneously Having Both Strength and Plastic Toughness Some existing stainless steel materials for highway guardrails sacrifice plastic toughness in pursuit of high strength, resulting in brittle fracture of the material when subjected to impact loads such as vehicle impacts, being unable to effectively buffer energy, and increasing the risk of overall structural damage of the guardrail.
[0005] (3) Insufficient Processing Performance Some stainless steel materials for highway guardrails are prone to work hardening during the processing process, especially during cold rolling, resulting in increased subsequent processing difficulty and reduced production efficiency. For example, some stainless steel materials with a relatively high carbon content have a significant increase in hardness after cold rolling and require multiple annealing treatments to continue processing, increasing production costs and production cycles.
[0006] 2. Difficulties Encountered in Solving These Problems (1) The Balance Problem of Alloy Composition Adjustment When attempting to improve the corrosion resistance, strength, plasticity, and toughness of stainless steel, it is necessary to adjust the alloy composition. However, the interactions between various alloying elements are complex, and adding one element may have a negative impact on other properties. For example, increasing the Mo element can enhance the chloride corrosion resistance, but excessive Mo may reduce the workability and toughness of the material. Finding the optimal balance among various properties is a huge challenge.
[0007] (3) Conventional austenitic stainless steels (such as 304 and 316L) have good corrosion resistance but low yield strength (usually 200 - 300 MPa). After cold rolling strengthening, the elongation after fracture will decrease significantly (<20%), and the product of tensile strength and elongation (TS×EL) is difficult to exceed 20 GPa·%, which cannot meet the requirements of highway guardrails for high strength and high plasticity. Chinese Patent CN 117026080 A developed a high-strength medium-nitrogen austenitic stainless steel plate and its preparation method. The high-strength austenitic stainless steel plate can achieve a maximum tensile strength of 1167 MPa through processes such as hot rolling, warm rolling, cold rolling, and rapid annealing, with an elongation after fracture of 41.2% and a product of tensile strength and elongation of 48.1 GPa·%, basically overcoming the dilemma of the balance between strength and plasticity. However, its process is complex and the elongation rate is relatively low.
[0008] (4) Highway guardrails are exposed to Cl⁻-containing environments (such as snow melting salts and coastal atmospheres) for a long time. Traditional stainless steels are prone to pitting corrosion and stress corrosion cracking (SCC). Especially after high-strength cold rolling, M 23 C6 carbides precipitate along the grain boundaries, increasing the risk of intergranular corrosion. Chinese Patent CN 102943219A developed a nickel-saving manganese-nitrogen-boron-containing austenitic stainless steel and its manufacturing method. It solved the problems of defects such as peeling and sand holes that are prone to occur during the cold rolling process, improved the surface quality and corrosion resistance of the product. However, in the wet-dry alternate test in a high-chloride snow melting agent medium, it is necessary to overcome the corrosion resistance under the corrosion service conditions of high-chloride snow melting agents, and the yield strength is relatively low, only 358 - 365 MPa.
[0009] (5) Conventional cold rolling (room temperature rolling) requires a large rolling force, resulting in large equipment losses and high energy consumption. Moreover, edge cracking is prone to occur under high deformation (the work hardening rate is too high). The cold rolling process has a significant impact on the microstructure and properties of stainless steel. To obtain ideal strength, plasticity, toughness, and workability, it is necessary to precisely control parameters such as the reduction ratio, rolling speed, and rolling temperature of cold rolling. However, these parameters are interrelated, and a slight change in any one parameter may lead to fluctuations in the performance of the final product. Therefore, it is necessary to develop a production process suitable for high-strength austenitic stainless steel. Summary of the Invention
[0010] The present invention overcomes the deficiencies of the prior art and provides a high-strength, high-ductility and highly corrosion-resistant austenitic stainless steel and a preparation method thereof; while taking into account strength and plasticity, the corrosion resistance of austenitic stainless steel is improved for stainless steel products in a specific service environment (de-icing agent service conditions).
[0011] The present invention is realized through the following technical solutions: A high-strength, high-ductility and highly corrosion-resistant austenitic stainless steel, the chemical composition by mass percentage is C: 0.07 wt.% - 0.15 wt.%, Mn: 6.0 wt.% - 10.0 wt.%, Cr: 13.0 wt.% - 16.0 wt.%, Ni: 0.5 wt.% - 2.0 wt.%, P: 0.05 wt.% - 0.07 wt.%, S ≤ 0.004 wt.%, N: 0.11 wt.% - 0.25 wt.%, Cu: 0.2 wt.% - 0.5 wt.%, and the rest is Fe.
[0012] Preferably, the chemical composition by mass percentage is C: 0.11 wt.%, Mn: 9.06 wt.%, Cr: 13.5 wt.%, Ni: 1.21 wt.%, P: 0.062 wt.%, S: 0.001 wt.%, N: 0.22 wt.%, Cu: 0.26 wt.%, and the rest is Fe.
[0013] A preparation method of a high-strength, high-ductility and highly corrosion-resistant austenitic stainless steel, comprising the following steps: S1. Smelt a billet according to the mass percentage of the chemical composition, obtain a steel billet through melting and casting, and forge the steel billet into a square billet after homogenization treatment; S2. Remove the scale on the surface of the square billet, and then perform multi-pass hot rolling on the square billet to obtain a hot-rolled plate, and cool the hot-rolled plate to room temperature in an air-cooling manner; S3. Perform isothermal treatment on the hot-rolled plate and then roll it on a cold rolling mill, repeat multiple times to obtain a warm-rolled plate, and finally cool it to room temperature by water cooling; the isothermal treatment is to keep the hot-rolled plate at 600 - 650 °C for 5 - 10 min in a medium-temperature furnace; the thickness of the warm-rolled plate is 2.0 - 2.5 mm; S4. First put the warm-rolled plate into a high-temperature furnace at 900 - 1000 °C for 3 - 5 min for short-time solution treatment, then put it into a medium-temperature furnace for interrupted annealing, and finally cool it to room temperature by water cooling.
[0014] Preferably, in step S1, the temperature of the homogenization treatment is 1200 °C - 1220 °C, and the holding time is 10 h - 15 h.
[0015] Preferably, the starting rolling temperature of the multi-pass hot rolling is 1120 °C - 1180 °C, and the final rolling temperature is 900 °C - 1100 °C.
[0016] Preferably, the thickness of the hot-rolled sheet obtained by multi-pass hot rolling is 3.5 mm - 4.5 mm.
[0017] Preferably, in step S4, the warm-rolled sheet after short-time solution treatment is put into a medium-temperature furnace at 500 - 600 °C for heat preservation for 2 - 3 min for interrupted annealing to obtain a final interrupted solution-treated warm-rolled sheet.
[0018] The beneficial effects of the present invention compared with the prior art are as follows: (1) Through the warm rolling + interrupted solution treatment process, nano-twins, recrystallized grains, stacking faults and controllable α'-martensite phase transformation are introduced into the austenite matrix, realizing the synergistic improvement of the tensile strength ≥ 1100 MPa and the elongation after fracture ≥ 55%, and the product of strength and plasticity ≥ 65 GPa·%.
[0019] (2) The high-strength and economical metastable austenitic stainless steel is used in highway guardrails for the first time. It replaces Ni element with Mn (6.0 - 10.0 wt.%) + N (0.05 - 0.25 wt.%), reducing the material cost by 15 - 20%. Through the assistance of Cu (0.5 - 1.5%) for passivation, the corrosion resistance is improved. Compared with traditional austenitic stainless steel, the usage amounts of Cr, Ni, and Mo elements are reduced, and the material cost is reduced by 15 - 20%. The high-strength and high-plasticity-product austenitic stainless steel described in the present invention has the characteristics of high strength and high plasticity product, which can be used in the highway guardrail traffic safety facilities industry for the first time.
[0020] (3) Through the warm rolling + interrupted solution treatment process, the proportion of Σ3 grain boundaries is increased. The interface energy of Σ3 grain boundaries is much lower than that of ordinary large-angle grain boundaries. The Σ3 grain boundary structure can effectively hinder the movement of dislocations during deformation and interrupted solution treatment, delay the initiation of cracks, thereby improving the elongation after fracture and work hardening ability of the material. The Σ3 grain boundary can promote the cross-interface slip or reflection of dislocations, avoid stress concentration, especially at low temperature or high strain rate, it can provide an additional deformation path, reduce local strain non-uniformity, and comprehensively improve the product of strength and plasticity of stainless steel materials through multiple factors working together.
[0021] (4) Through the warm rolling + interrupted solution treatment process, the proportion of Σ3 grain boundaries is increased. The coherency of Σ3 grain boundaries reduces the active sites, inhibits the tendency of pitting corrosion and intergranular corrosion. In an environment containing high Cl⁻ (service environment of deicing salt medium), the passivation film formed in the Σ3 grain boundary region is denser and has fewer defects, delaying the corrosion propagation. The warm rolling + interrupted solution treatment sample has a large passivation interval and a low self-corrosion current density. Description of the Drawings
[0023] Figure 1 It is the process diagram of the method described in Example 1; Figure 2 It is the process diagram of the method described in Comparative Example 1; Figure 3 Process drawing of the method described in Comparative Example 2; Figure 4 KAM + ∑3 grain boundary map of Example 1; Figure 5 KAM + ∑3 grain boundary map of Comparative Example 1; Figure 6 KAM + ∑3 grain boundary map of Comparative Example 2; Figure 7 Polarization curves of specimens with different processes in high - concentration chloride - based snow - melting agent; (red line is for Example 1, blue line is for Comparative Example 1, and black line is for Comparative Example 2). Specific implementation manners
[0024] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention clearer and more understandable, the present invention will be further described in detail in combination with examples and drawings. It should be understood that the specific examples described herein are only used to explain the present invention and are not used to limit the present invention. The technical solutions of the present invention will be described in detail below in combination with examples and drawings, but the protection scope is not limited by this.
[0025] Example 1 This example provides an austenitic stainless steel for highway guardrails with high corrosion resistance and high strength - plasticity product, and a preparation method thereof. The chemical composition of the austenitic stainless steel is as follows by mass percentage: C: 0.11 wt.%, Mn: 9.06 wt.%, Cr: 13.5 wt.%, Ni: 1.21 wt.%, P: 0.062 wt.%, S: 0.001 wt.%, N: 0.22 wt.%, Cu: 0.26 wt.%, and the rest is Fe. A preparation method of a warm - rolled austenitic stainless steel for highway guardrails with high corrosion resistance and high strength - plasticity product, specifically the following steps: S1. Smelt the casting blank according to the mass percentage of the chemical composition, obtain the steel blank through melting and pouring, and forge it into a square blank after homogenization treatment; Specifically, the temperature of the homogenization treatment is 1220 °C, and the holding time is 12 h.
[0026] S2. Remove the scale on the surface of the square blank, and perform multi - pass hot rolling such as rough rolling and finish rolling on the square blank after scale removal to obtain a hot - rolled sheet, and cool the hot - rolled sheet to room temperature by air cooling; The starting rolling temperature of the multi - pass hot rolling is 1145 °C, the final rolling temperature is 900 °C, and it is air - cooled to room temperature; The thickness of the hot - rolled sheet obtained through multi - pass hot rolling is 4.0 mm.
[0027] S3. Take out the hot-rolled plate after short-time annealing in a medium-temperature furnace, and obtain a warm-rolled plate through 3 passes of rolling on a cold rolling mill (repeat the isothermal and warm rolling processes), and finally water-cool to room temperature; Specifically, the operation is as follows: Keep the hot-rolled plate at 650 °C for 5 minutes, take out the hot-rolled plate, reduce its thickness to 3.0 mm through 3 passes of rolling on a cold rolling mill, then repeat the operation of keeping the hot-rolled plate at 650 °C for 5 minutes, taking out the hot-rolled plate, and performing 3 passes of rolling on the cold rolling mill 2 times to reach the target thickness of 2.0 mm.
[0028] S4. First put the warm-rolled plate into a high-temperature furnace for short-time solution treatment, then put it into a medium-temperature furnace for interrupted solution treatment, and finally water-cool to room temperature.
[0029] Specifically, place the warm-rolled plate in a high-temperature furnace at 900 °C for 4 minutes, then take out the warm-rolled plate and put it into a medium-temperature furnace at 650 °C for 2 minutes to obtain the finally interrupted solution-treated warm-rolled plate.
[0030] Wire cut samples are taken from the austenitic stainless steel for high-corrosion-resistant and high strength-ductility product highway guardrails prepared in Example 1. After that, the surface of the longitudinal × transverse samples is successively polished with sandpapers from 240# to 5000#, and then electrochemically polished with 20% perchloric acid alcohol. The electrochemically polished samples are subjected to EBSD-KAM and special grain boundary block analysis, and the proportion of Σ3 grain boundaries is obtained as 54.9%.
[0031] Electrochemical experiments are carried out on the interrupted solution-treated warm-rolled plate. The corrosion medium is selected as a snowmelt agent, and its mass ratio is NaCl:MgCl2:CaCl2 = 6:2:2. The scanning range of the polarization curve is -1.0 V to 0.5 V, the potential scanning speed is 1 mV / s, and the impedance test frequency range is 100 kHz to 10 mHz. The potentiodynamic polarization curve is obtained, and the passivation interval of the sample is obtained. Its passivation interval is 0.15 V to 0.4 V.
[0032] Comparative Example 1 The chemical composition and mass percentage of the austenitic stainless steel used in Comparative Example 1 are the same as those in Example 1; however, a different preparation method is adopted from that in Example 1: S1. Smelt and cast billets according to the mass percentage of chemical composition, obtain steel billets through melting and pouring, and forge them into square billets after homogenization treatment; the temperature of the homogenization treatment is 1220 °C, and the holding time is 12 h; S2. Remove the surface scale of the square billet, and perform multi-pass hot rolling such as rough rolling and finish rolling on the square billet after scale removal to obtain hot-rolled sheets, and cool the hot-rolled plate to room temperature by air cooling; The starting rolling temperature of the multi-pass hot rolling is 1145 °C, the final rolling temperature is 900 °C, and it is air-cooled to room temperature. The thickness of the hot-rolled plate obtained through multi-pass hot rolling is 4.0 mm.
[0033] Wire cut sampling was performed on the hot-rolled plate prepared in Comparative Example 1. After that, the surface of the longitudinal × transverse specimen was successively polished with sandpapers from 240# to 5000#, and then electrolytically polished with 20% perchloric acid alcohol. The electrolytically polished specimen was subjected to EBSD-KAM and special grain boundary block analysis, and the Σ3 grain boundary ratio was obtained as 43.3%.
[0034] An electrochemical experiment was carried out on the hot-rolled plate prepared in Comparative Example 1. The corrosion medium was a snow melting agent, and its mass ratio was NaCl:MgCl2:CaCl2 = 6:2:2. The polarization curve scanning range was -1.0 V to 0.5 V, the potential scanning speed was 1 mV / s, and the impedance test frequency range was 100 kHz to 10 mHz. The potentiodynamic polarization curve was obtained, and the passivation range of the specimen was obtained. Its passivation range was 0.22 V to 0.35 V, and the passivation range was smaller than that of the example.
[0035] Comparative Example 2 The chemical composition and mass percentage of the austenitic stainless steel used in Comparative Example 2 were the same as those in Example 1; however, a different preparation method was used from that in Example 1: S1. The billet was smelted according to the mass percentage of the chemical composition, and the steel billet was obtained through melting and casting. After homogenization treatment of the steel billet, it was forged into a square billet; the homogenization treatment temperature was 1220 °C, and the holding time was 12 h.
[0036] S2. The surface scale of the square billet was removed, and the square billet after scale removal was subjected to multi-pass hot rolling such as rough rolling and finish rolling to obtain a hot-rolled plate, and the hot-rolled plate was cooled to room temperature by air cooling; The starting rolling temperature of the multi-pass hot rolling was 1145 °C, the final rolling temperature was 900 °C, and it was air-cooled to room temperature; the thickness of the hot-rolled plate obtained through multi-pass hot rolling was 4.0 mm.
[0037] S3. The hot-rolled plate was taken out after short-time annealing in a medium-temperature furnace, and was rolled through 3 passes on a cold rolling mill to obtain a warm-rolled plate (repeating the isothermal and warm rolling processes), and finally water-cooled to room temperature; The specific operation was as follows: the hot-rolled plate was held at 650 °C for 5 min, the hot-rolled plate was taken out, and it was rolled through 3 passes on a cold rolling mill to be thinned to 3.0 mm. Subsequently, the operation of holding at 650 °C for 5 min, taking out the hot-rolled plate, and rolling through 3 passes on a cold rolling mill was repeated 2 times to reach the target thickness of 2.0 mm.
[0038] Wire cut sampling was performed on the final plate prepared in Comparative Example 2. After that, the surface of the longitudinal × transverse specimen was successively polished with sandpapers from 240# to 5000#, and then electrolytically polished with 20% perchloric acid alcohol. The electrolytically polished specimen was subjected to EBSD-KAM and special grain boundary block analysis, and the Σ3 grain boundary ratio was obtained as 44.7%.
[0039] The interrupted solution annealing warm rolling specimens were subjected to electrochemical experiments. The corrosion medium was selected as snow melting agent, and its mass ratio was NaCl:MgCl2:CaCl2 = 6:2:2. The scanning range of the polarization curve was -1.0 V to 0.5 V, the potential scanning rate was 1 mV / s, and the impedance test frequency range was 100 kHz to 10 mHz. The potentiodynamic polarization curve was obtained, and the passivation interval of the specimen was obtained. The passivation interval was 0.22 V to 0.30 V, which was smaller than the passivation interval of the example.
[0040] The above content is a further detailed description of the present invention in combination with specific preferred embodiments. It cannot be determined that the specific embodiments of the present invention are limited thereto. For those of ordinary skill in the technical field to which the present invention pertains, without departing from the premise of the present invention, several simple deductions or substitutions can be made, and all should be regarded as belonging to the patent protection scope determined by the claims submitted for the present invention.
Claims
1. A high-strength, high-ductility and high-corrosion-resistant austenitic stainless steel, characterized in that: The chemical composition by mass percentage is C: 0.07 wt.%~0.15 wt.%, Mn: 6.0 wt.%~10.0 wt.%, Cr: 13.0 wt.%~16.0 wt.%, Ni: 0.5wt.%~2.0 wt.%, P: 0.05 wt.%~0.07 wt.%, S≤0.004 wt.%, N: 0.11 wt.%~0.25 wt.%, Cu: 0.2wt.%~0.5 wt.%, and the rest is Fe.
2. The high-strength, high-ductility and high-corrosion-resistant austenitic stainless steel according to claim 1, characterized in that: The chemical composition by mass percentage is C: 0.11 wt.%, Mn: 9.06 wt.%, Cr: 13.5 wt.%, Ni: 1.21 wt.%, P: 0.062wt.%, S: 0.001 wt.%, N: 0.22 wt.%, Cu: 0.26 wt.%, and the rest is Fe.
3. The method for preparing a high-strength, high-ductility and high-corrosion-resistant austenitic stainless steel according to claim 1 or 2, characterized in that: The following steps are involved: S1. Smelting a cast billet according to the mass percentage of chemical composition, obtaining a steel billet by melting and pouring, and forging the steel billet into a square billet after homogenizing the steel billet; S2, removing the iron oxide scale on the surface of the square billet, and then performing multiple hot rolling on the square billet to obtain a hot-rolled plate, and cooling the hot-rolled plate to room temperature by air cooling; S3, the hot-rolled plate is subjected to isothermal treatment and then rolled on a cold rolling unit, and the process is repeated several times to obtain a warm-rolled plate, and finally water-cooled to room temperature; the isothermal treatment is to keep the hot-rolled plate at 600-650°C in a medium temperature furnace for 5-10 minutes; the thickness of the warm-rolled plate is 2.0-2.5 mm; S4. Place the warm rolled plate in a high temperature furnace at 900-1000℃ for 3-5 minutes for short-time solid solution treatment, then place it in a medium temperature furnace for interrupted annealing, and finally cool it to room temperature with water.
4. The method for preparing austenitic stainless steel with high strength, plasticity and corrosion resistance according to claim 3, characterized in that: In step S1, the temperature of the homogenization treatment is 1200°C-1220°C, and the holding time is 10 h-15 h.
5. The method for preparing austenitic stainless steel with high strength, plasticity and corrosion resistance according to claim 3, characterized in that: The starting rolling temperature of the multi-pass hot rolling is 1120°C-1180°C, and the finishing rolling temperature is 900°C-1100°C.
6. The method for preparing austenitic stainless steel with high strength, plasticity and corrosion resistance according to claim 3, characterized in that: The thickness of the hot rolled plate obtained by multiple hot rolling is 3.5 mm-4.5 mm.
7. The method for preparing austenitic stainless steel with high strength, plasticity and corrosion resistance according to claim 3, characterized in that: In step S4, the warm rolled plate after short-time solid solution treatment is placed in a medium temperature furnace at 500-600°C and kept at this temperature for 2-3 minutes for interrupted annealing to obtain a final interrupted solid solution warm rolled plate.
Citation Information
Patent Citations
Nickel-saving austenitic stainless steel containing manganese, nitrogen and boron and fabrication method
CN102943219A
High-strength medium-nitrogen austenitic stainless steel plate and preparation method
CN117026080A
Cited By
An ultra-high-strength plastic hetero-layer structure copper-containing austenitic stainless steel and a preparation method thereof
CN122811632A